2018
DOI: 10.15761/jtbr.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in psychiatric disorders

Abstract: The study of quality of life and subjective wellbeing of patient is a recent phenomenon which has gained attention only in last two decades. Less attention was given to treating long term impairement and chronic illness. Rather cure was given more importance. However, this trend has changed, and it has shifted to the concept of quality of life. Now the goal of treatment is to give the patient good quality of life, this becomes more important in cases where cure is impossible or there is long term impairements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Additionally, many QoL assessments that are disease-specific also include measures for social and psychological domains [ 21 , 22 ]. Psychological distress is a strong predictor of poor QoL, independent of physical and social factors [ 23 , 24 ]. Moreover, psychological distress is a primary factor in vulnerability to addiction and in treatment retention and relapse [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many QoL assessments that are disease-specific also include measures for social and psychological domains [ 21 , 22 ]. Psychological distress is a strong predictor of poor QoL, independent of physical and social factors [ 23 , 24 ]. Moreover, psychological distress is a primary factor in vulnerability to addiction and in treatment retention and relapse [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is of importance and suggests that additional mental health conditions, or difficulties associated with mental health, may impact overall health-related well-being to a higher degree than additional physical health conditions. Given the impact that mental health has been found to have on general health and well-being in non-veteran populations (Chaudhury et al, 2018; Connell et al, 2012; World Health Organization, 2004), this finding warrants further investigation in this cohort. Furthermore, this study identified issues with the applicability of the WBI finance questions for older veterans, and a possible need to support working-age blind veterans in preparing financially for the future.…”
Section: Discussionmentioning
confidence: 88%
“…Direct policymakers to take interest in stakeholders and provide appropriate treatment. [11][12][13][14][15][16][17][18][19]…”
Section: Need Of Restoring Quality Of Life In Depression Disordermentioning
confidence: 99%